MENGGUGAT DIKSI DAN EKSPRESI ANAK PADA PUISI ANAK MAJALAH BOBO - Muhamad Haryanto (LPPM Universitas Pekalongan, 2012)
Child poem and adult poem talk about life. However, they are different in expressing and dealing with it because they have different maturity and point of view. Child expressions in poem vary from trivial, funny, habit, nature, ream, religiosity, love and so on. Those expressions are conveyed through simple dictions. Bobo magazine is child magazine which give space for literary expressions specially child poems. In Bobo child poems, there is unique expression in choosing diction and variations. Keywords: child poems, expresson, diction, Bobo magazine